The AICHR as a participatory space: contesting the secretive face of power. Issue 4 (4th July 2022) - Collins, Alan; Bon Tai Soon, Edmund
ABSTRACT: The ASEAN Intergovernmental Commission on Human Rights (AICHR) is often regarded unfavourably, depicted at best as irrelevant in the battle to promote and protect human rights in Southeast Asia, and at worst, complicit in the abuse of human rights by its silence in the face of the region's human rights' tragedies. While AICHR has many limitations, we regard it as a work-in-progress, evolving as it was always meant to. To understand this evolution, we conceive of AICHR as a participatory space in which contestation of what AICHR can, and cannot, do is being undertaken by its Representatives. This contestation includes exposing its secretive face of power by revealing: the space human rights can be discussed in; who can participate and who is excluded in this discussion; and how malleable the norms that operate within this space are to change. The latter aspect of contestation engages with the thorny 'problem' of consensus. We argue that the presence of Representatives from outside of government has introduced a desire in AICHR for change; a dynamism that makes it a participatory space witnessing contestation that has the potential to enable AICHR to evolve. A space, therefore, that for all its shortcomings is worth watching.